#JeSuisCharlie? Hashtags as narrative resources in contexts of ecstatic sharing. (April 2018) - Giaxoglou, Korina
Highlights: Hashtagging discourse practice involves storying as sharing. Hashtags serve metalinguistic, metadiscourse and metanarrative functions. Ecstatic sharing is centered on the affective intensity of the here-and-now. Ecstatic sharing is a site of narrative stancetaking that creates dividing lines of evaluation and identification. Abstract: Uses of hashtags as storytelling devices have received little attention so far in the field of sociolinguistics and discourse analysis. This article seeks to fill this gap by providing a narrative-discourse perspective on how hashtags are used as resources for sharing and story making (Androutsopoulos, 2014; Georgakopoulou, 2015a, 2015b, in press), foregrounding narrative as a circulatory drive on social media. The data for analysis are drawn from Twitter and the Guardian 's rolling coverage of the deadly attacks at the satirical magazine Charlie Hebdo offices on January 7th, 2015. The analysis looks at the emergence and circulation of hashtags #CharlieHebdo and #JeSuisCharlie in their polylingual instantiations. Its findings point to the hashtags' metalinguistic, metadiscursive and metanarrative functions in relation to positions of narrative stancetaking made available to networked publics. It is argued that hashtag sharing in this case attests to a shift from modes of ecstatic global news reporting and spectatorships of suffering (Chouliaraki, 2006) to modes of ecstatic sharing on social media which create dividing lines of evaluative assessments of the events. The study contributes to the empirical study of hashtagging as social and discourse practice.